Analisis Akuntabilitas Pelayanan Kenaikan Pangkat Pegawai Negeri Sipil: Studi Kasus Penerapan SAPK BKN di BKD Provinsi Sumatera Selatan - Dian Ekawati; Mega Nugraha; Muhammad Ervan Marzuki (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Dian Ekawati. Analysis of Accountability for Promotion of Civil Servant Ranks (Case Study of Application of SAPK BKN in BKD, South Sumatra Province). Accountability of Service Promotion for Civil Servants (Case Study of Application of SAPK BKN in BKD of South Sumatra Province) has basically been going well, but because there were some disturbances related to network problems and application system problems, so there were some things that were delayed in the management process. . It has not been added to the terms and files that are not appropriate so that many promotion files have not been approved and must be repaired. The supporting factor is the existence of technological advances that become service innovations, in the form of online applications, namely online SAPK in the management of promotions, it will provide convenience in the management of promotions. The inhibiting factor is that the existence of signal interference in several districts is a weak side of the online system that must be improved, as well as the requirements for completeness of files that have not been met by employees hampering the approval process for promotions.